The Ethnoscience Approach in Science Education and Its Impact on Students’ Scientific Literacy: A Literature Review - Gesti Maharani; Sura Juddin; Nada Clairina Sophian (Indonesian Journal of Innovation and Educational Technology, 2026)
This study aims to analyze the role of integrating ethnoscience in science learning in improving students’ scientific literacy. The method used is a systematic literature review by analyzing 33 relevant scientific articles. Data were collected through document analysis and examined using a qualitative descriptive approach to identify patterns of ethnoscience integration and its impact on scientific literacy. The results of the review indicate that ethnoscience is integrated into science learning through various forms, such as inquiry-based learning models, Project-Based Learning (PjBL), and STEM approaches, as well as through the development of teaching materials, learning media, and assessment instruments based on local wisdom. The implementation of ethnoscience is most commonly found at the junior and senior high school levels, where students are able to relate scientific concepts to cultural contexts. This integration has been proven to improve students’ scientific literacy, particularly in understanding concepts, explaining scientific phenomena, using scientific evidence, and developing critical thinking and problem-solving skills. The findings conclude that ethnoscience is an effective and contextual learning approach in enhancing students’ scientific literacy. Therefore, ethnoscience has great potential to be further developed in science education to support meaningful learning that is relevant to real-life contexts and the demands of the 21st century.